EHD1 functions in endosomal recycling and confers salt tolerance. - Maya Bar; Meirav Leibman; Silvia Schuster; Hilla Pitzhadza; Adi Avni (PLoS ONE, 2013)
Endocytosis is a crucial process in all eukaryotic organisms including plants. We have previously shown that two Arabidopsis proteins, AtEHD1 and AtEHD2, are involved in endocytosis in plant systems. Knock-down of EHD1 was shown to have a delayed recycling phenotype in mammalians. There are many works in mammalian systems detailing the importance of the various domains in EHDs but, to date, the domains of plant EHD1 that are required for its activity have not been characterized. In this work we demonstrate that knock-down of EHD1 causes a delayed recycling phenotype and reduces Brefeldin A sensitivity in Arabidopsis seedlings. The EH domain of EHD1 was found to be crucial for the localization of EHD1 to endosomal structures. Mutant EHD1 lacking the EH domain did not localize to endosomal structures and showed a phenotype similar to that of EHD1 knock-down seedlings. Mutants lacking the coiled-coil domain, however, showed a phenotype similar to wild-type or EHD1 overexpression seedlings. Salinity stress is a major problem in current agriculture. Microarray data demonstrated that salinity stress enhances the expression of EHD1, and this was confirmed by semi quantitative RT-PCR. We demonstrate herein that transgenic plants over expressing EHD1 possess enhanced tolerance to salt stress, a property which also requires an intact EH domain.